Acylation of nitrobenzene and substituted nitrobenzenes by benzoyl chloride using GaClx- and GaAlClx-grafted meporous Si-MCM-41 catalysts - Choudhary, Vasant R.; Jha, Rani (Microporous and Mesoporous Materials, 2009)
A acylation of nitrobenzene and substituted nitrobenzene by benzoyl chloride can be accomplished with good yield in a short reaction period (<= 3 h), even in the presence of moisture, using GaClx- and GaAlClx-grafted mesoporous silica (Si-MCM-41) catalyst. The catalyst is reusable/environmentally friendly. The presence of moisture in the catalyst has beneficial effect on the acylation reaction. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Acylation; Benzoyl chloride; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; nitrobenzene